Alih Kode Dalam Novel Ocean Marine Karya Snow Sparkle dan Implikasinya Dalam Pembelajaran Bahasa Indonesia Di SMK - Nova Yulia; Alifiah Nurachmana; Petrus Poerwadi; Yuliati Eka Asi; Nirena Ade Christy (Universitas Palangka Raya, 2024)
The aims of the research are (1) to describe the form of external code switching found in the novel Ocean Marine by Snow Sparkle, (2) to describe the factors that cause code switching to occur in the novel Ocean Marine by Snow Sparkle, (3) to describe the function of code switching extern in the novel Ocean Marine by Snow Sparkle, and (4) describe the implications of research results in learning Indonesian at vocational schools. This research is a qualitative descriptive study. Qualitative descriptive research aims to describe, depict, explain, explain and answer in more detail the problems to be studied by studying as closely as possible an individual, a group or an event. This sociolinguistic research focuses on the aspect of code switching. The data source in this research is the novel Ocean Marine by Snow Sparkle. The data in this research are phrases, clauses and sentences in the novel Ocean Marine by Snow Sparkle which were identified as containing code switching. The data collection techniques used in this research are non-participant observation techniques and documentation techniques. The research results from the analysis of the use of code switching in the novel Ocean Marine by Snow Sparkle are as follows. 1) The form of external code switching in the novel Ocean Marine by Snow Sparkle which is divided into phrase level, clause level, sentence level and inter-sentence level. 2) Factors causing external code switching in the novel Ocean Marine by Snow Sparkle which consist of the speaker, speech partner, change in situation, change from formal to informal, and change in topic of conversation. 3) The function of external code switching in the novel Ocean Marine by Snow Sparkle is divided into three, namely emphasizing and clarifying statements, quoting other people's conversations, and avoiding rough forms and subtle forms. 4) This research is implied in the Indonesian language module of the Merdeka curriculum for class XI even semester in phase F learning outcomes related to Drama material with sub-theme C Analyzing Linguistic Rules of Drama Text.